VISUAL SEMIOTIC ANALYSIS OF GAMIFICATION ELEMENTS IN DUOLINGO GERMAN - Azah Afifah; Odi Nurdiawan; Arif Rinaldi Dikananda (PT. Berkah Digital Teknologi, 2026)
The advancement of digital technology has accelerated the growth of Mobile Assisted Language Learning (MALL), with Duolingo as one of the most popular gamified language-learning applications. This study analyzes the visual semiotics of gamification elements in the Duolingo German interface (versions 2022–2025). A descriptive qualitative approach with a case study design is employed. Data consist of screenshots of gamification elements (XP, streak, badges, leaderboard, mascot, and feedback animations) and related literature, analyzed using Roland Barthes’ semiotics, the Shannon and Weaver communication model, and Self Determination Theory within a sociocultural framework. The findings show that visual gamification elements construct the myth of an ideal learner who is always productive, consistent, and competitive. These elements have a dual motivational effect: they can both strengthen and undermine the needs for competence, autonomy, and relatedness, depending on users’ cultural context and meaning-making. The study enriches visual semiotics and gamified language learning research and offers UI/UX recommendations for developers and educators to design more humanistic and meaningful learning experiences. Abstrak Kemajuan teknologi digital telah mempercepat pertumbuhan Pembelajaran Bahasa Berbantuan Seluler (Mobile Assisted Language Learning/MALL), dengan Duolingo sebagai salah satu aplikasi pembelajaran bahasa berbasis gamifikasi yang paling populer. Studi ini menganalisis semiotika visual elemen gamifikasi dalam antarmuka Duolingo Jerman (versi 2022–2025). Pendekatan kualitatif deskriptif dengan desain studi kasus digunakan. Data terdiri dari tangkapan layar elemen gamifikasi (XP, streak, lencana, papan peringkat, maskot, dan animasi umpan balik) dan literatur terkait, yang dianalisis menggunakan semiotika Roland Barthes, model komunikasi Shannon dan Weaver, dan Teori Penentuan Diri dalam kerangka sosiokultural. Temuan menunjukkan bahwa elemen gamifikasi visual membangun mitos tentang pembelajar ideal yang selalu produktif, konsisten, dan kompetitif. Elemen-elemen ini memiliki efek motivasi ganda: mereka dapat memperkuat dan melemahkan kebutuhan akan kompetensi, otonomi, dan keterkaitan, tergantung pada konteks budaya dan pemahaman makna pengguna. Studi ini memperkaya semiotika visual dan penelitian pembelajaran bahasa yang digamifikasi, serta menawarkan rekomendasi UI/UX bagi pengembang dan pendidik untuk merancang pengalaman belajar yang lebih humanistik dan bermakna.